(untitled) (Applied Biological Research, 2014)
This in vitro study was aimed to compare the kinetic properties of acetyl cholinesterase (AChE) in two model systems i.e. rat brain homogenate and nematode model Caenorhabditis elegans. These models were analyzed with basic kinetic parameters viz., substrate hydrolysis, inhibition pattern, determined Km, Vmax, IC50, KI and Vimax using dichlorvos (DDVP), an organophosphorus compound widely used for insect-pest control in agricultural crops. The rat brain homogenate exhibited Km, Vmax and IC50 values of 59 M, 33 nmol min-1 mg-1protein and 107.18 ± 3.56 nM, respectively, for rat brain homogenate. C. elegans homogenate exhibited Km, Vmax and IC50 values of 725.41 M, 112.35 nmol min-1 mg-1protein and 45.7 ± 2.68 nM, respectively. The pattern of inhibition was irreversible in both the systems. The study showed that C. elegans in vitro system can be used as a model to establish the inhibition pattern of organophosphorus compounds (known inhibitors of AChE) as compared to traditionally used rat brain homogenate system.